1996
DOI: 10.1097/00000542-199605000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Anesthetics Selectively Inhibit the Calcium sup 2+ -transporting ATPase in Neuronal and Erythrocyte Plasma Membranes

Abstract: The findings demonstrate analogous response of the PMCA of neuronal and erythrocyte cells to two groups of general anesthetics. The PMCA activity is selectively inhibited by volatile anesthetics at their clinical concentrations. The enzyme in vivo may then be a pharmacologic target for volatile anesthetics but not for barbiturates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…By light microscopy, the preparation appears as microvascular segments, predominantly vascular smooth muscle, with occasional adherent pericytes. To validate functional viability, we measured steady-state Na+-K+ ATPase activity as previously described (Fomitcheva and Kosk-Kosicka, 1996). Enzyme activity was preserved in the microvascular preparation at 4.4 !Lm P/mg protein per hour.…”
Section: Methodsmentioning
confidence: 99%
“…By light microscopy, the preparation appears as microvascular segments, predominantly vascular smooth muscle, with occasional adherent pericytes. To validate functional viability, we measured steady-state Na+-K+ ATPase activity as previously described (Fomitcheva and Kosk-Kosicka, 1996). Enzyme activity was preserved in the microvascular preparation at 4.4 !Lm P/mg protein per hour.…”
Section: Methodsmentioning
confidence: 99%
“…It was hypothesized that the effects are based on an intracellular pH change due to interactions of increased free Ca 2+ -concentrations with the protonation of hemoglobin 20 , 21 . Further increasing the concentration to a MAC of approximately 3 was also shown to inhibit several types of ATPase like the Na + -K + -ATPase or the Mg 2+ -ATPase 19 . This may partially explain the underlying mechanisms behind the opponent effects on Hb-O 2 affinity when progressing the dose to rather high concentrations, as observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the production of NAPDH was reduced, hence exposing the red blood cell to reactive oxygen species 18 . Fomitcheva et al showed that isoflurane in clinically relevant concentrations inhibits the activity of plasma membrane Ca 2+ -transporting adenosine triphosphatase (PMCA), thus increasing intracellular Ca 2+ concentrations 19 . This increase was linked to a right shift of the ODC and a lower affinity for oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetics (VAs) inhibit the activity and Ca 2+ transport of the plasma membrane Ca 2+ ‐ATPase (PMCA) [1–3]. The two best studied activation pathways of the enzyme, proceeding through either calmodulin binding to PMCA monomers or enzyme dimerization, are inhibited in a dose‐dependent manner and with a similar I 50 by several VAs used in clinical practice, including halothane, isoflurane, and methoxyflurane [1,4].…”
mentioning
confidence: 99%